Mekanisme Koping Keluarga Yang Anggota Keluarganya Dirawat Di Ruang lcu Rumah Â Sakit Islam Sakinah - Windartik, Emyk; Hari Subakti, Mochammad (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstractFamily coping mechanism is the way in which the family in solving problems, adapt to change, and the response to the situation. The purpose of this study was to determine the coping mechanisms of families whose family members were treated in the Intensive Care Unit Hospital Islam Sakinah Mojokerto. This study was descriptive. Its population is the family members of patients admitted to the Intensive Care Unit Hospital Islam Sakinah Mojokerto many as 43 people to obtain a sample of20 people taken by consecutive sampling. The variable in this study is the family coping mechanism whose family members were treated in the Intensive Care Lnit. Collecting data in this study were taken using a questionnaire. The results showed that nearly all respondents using adaptive coping mechanisms as much as 17 respondents (89.5%) it can be seen from the results of research that one partial role played by the family in addressing theexisting issues diruang family members hospitalized Intensive Care Unit is by talking with others. Tt is influenced by theirage, the majority of respondents were aged above 35 years were 12 respondents (63.2%). As more and more aged people, the better the coping mechanism against something, because the growing adult thinking and attitude in each individual behaves. With so try as often as possible for respondents to ask or consult with a nurse about the changes that happen to a family member being treated in the Intensive Care llnit, and could pose coping well.Keywords : Family Coping Mechanism